Evaluation of automated pre-treatment and transit in-vivo dosimetry in radiotherapy using empirically determined parameters. (October 2020) - Bossuyt, Evy; Weytjens, Reinhilde; Nevens, Daan; De Vos, Sarah; Verellen, Dirk
Highlights: In-vivo transit dosimetry efficiently reveals a wide variety of deviations. In-vivo transit dosimetry shows potential to serve as a base for adaptive planning. Tolerance levels should balance false positive and relevant true positive results. Parameters for gamma analysis can be determined empirically. Pre-treatment and in-vivo results are dependent on machine type. Abstract: Background and purpose: First reports on clinical use of commercially automated systems for Electronic Portal Imaging Device (EPID)-based dosimetry in radiotherapy showed the capability to detect important changes in patient setup, anatomy and external device position. For this study, results for more than 3000 patients, for both pre-treatment verification and in-vivo transit dosimetry were analyzed. Materials and methods: For all Volumetric Modulated Arc Therapy (VMAT) plans, pre-treatment quality assurance (QA) with EPID images was performed. In-vivo dosimetry using transit EPID images was analyzed, including causes and actions for failed fractions for all patients receiving photon treatment (2018–2019). In total 3136 and 32, 632 fractions were analyzed with pre-treatment and transit images respectively. Parameters for gamma analysis were empirically determined, balancing the rate between detection of clinically relevant problems and the number of false positive results. Results: Pre-treatment and in-vivo results depended on machine type. Causes for failed in-vivo analysis included deviations in patient positioning (32%) and anatomy change (28%). In addition, errors in planning, imaging, treatment delivery, simulation, breath hold and with immobilization devices were detected. Actions for failed fractions were mostly to repeat the measurement while taking extra care in positioning (54%) and to intensify imaging procedures (14%). Four percent initiated plan adjustments, showing the potential of the system as a basis for adaptive planning. Conclusions: EPID-based pre-treatment and in-vivo transit dosimetry using a commercially available automated system efficiently revealed a wide variety of deviations and showed potential to serve as a basis for adaptive planning.